Causes of xerostomia in the cancer treatment - Minicucci, Eliana Aparecida [UNESP]; Weber, Silke Anna Theresa [UNESP]; da Silva, Glenda Nicioli (My University, 2014)
Saliva is fundamental for the maintenance of oral health. It is a complex mix of fluids secreted by major and minor salivary glands. Xerostomia is the subjective sensation of dry mouth, that can be associated or not to the diminution of the salivary flow. It predominantly affects middle aged and elderly people with an estimated prevalence of 21% and 27% in men and women, respectively. Oral dryness can profoundly affect the quality of life, interfering to basic daily functions such as chewing, swallowing and speaking. Reduction of volume and the antibacterial properties of saliva may cause infections, accelerate tooth decay and periodontal disease. The most important causes of xerostomia include factors that act on the salivary center in the central nervous system related to emotions; the autonomic nervous system caused by encephalitis, cerebral tumors, cerebral vascular accidents, neurosurgery or drugs; autoimmune disease, viral or bacteria salivary gland infections, radiotherapy and chemotherapy and the hydro- electrolytic balance related to cystic fibrosis, primary cirrhoses, sarcoidosis, amyloidosis, hypothireoidism and hemochromatosis. The oral epithelium has a high turn over, therefore is one of the main places in which manifest the side effects of chemotherapy (CT) and head and neck radiotherapy (RT). The xerostomia caused by RT can be due to indirect damage to epithelial and connective tissue elements of the gland, or direct damage to salivary acini and ducts. High-dose chemotherapy may affect the salivary flow, principally in hematopoietic cell transplantation, total body irradiation and concurrent medications.